The 1951 United Nations Convention Relating to the Status of Refugees: Contemporary Theory and Practice - Béres, Nóra (Migration and Central Europe: Challenges and Legal Responses, 2024)
This chapter seeks to provide an analysis on the framework of interpretation of the 1951 United Nations Convention relating to the Status of Refugees with special regard to its key elements: the definition of the term ‘refugee’, the concept of refugee status (including illegal entry to a country), and the principle of non-refoulement. When it comes to the application of the provisions enshrined under the Convention, the fact that that neither a treaty body nor a human rights monitoring mechanism were set up by the drafters must be taken into consideration. Nevertheless, as an ultimate source of international law, the Convention is regularly and variously interpreted by both international courts and national tribunals, and in addition to legal scholarship, judicial case law operates as a guide in determining the real essence and meaning of the Convention’s provisions. In this vein, this chapter applies concept analysis and legal case analysis as methodology to discuss in detail the most significant norms of contemporary international refugee law.Keywords: Refugee Convention, refugee definition, refugee status, illegal entry to a country, non-refoulement